2021
DOI: 10.12775/jehs.2021.11.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Similar and specific immunotropic effects of sulfate-chloride sodium-magnesium mineral waters "Myroslava" and "Khrystyna" of Truskavets’ spa in healthy female rats

Abstract: Background. Earlier in an experiment on rats, we showed that newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets’ spa has a significant modulating effect on the parameters of metabolism and the autonomic nervous and endocrine systems. In this study, conducted in line with the concepts of neuroendocrine-immune complex and functional-metabolic continuum, data on the immunomodulatory effects of these waters on the same rats. Materials and Methods. Experiment was performed on 50 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In addition, it should be borne in mind that our patients used this water in combination with biologically active water Naftussya. However, the specificity of physiological effects was confirmed in an experiment on rats [1,9,10,11,24].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it should be borne in mind that our patients used this water in combination with biologically active water Naftussya. However, the specificity of physiological effects was confirmed in an experiment on rats [1,9,10,11,24].…”
Section: Discussionmentioning
confidence: 98%
“…Earlier in experiments on rats, it was shown that drinking mineral water, regardless of their mineralization and chemical composition, have similar (nonspecific) course effects on a number of parameters of metabolism and neuroendocrine-immune complex [1,10,11,23,36]. The aim of this study is to identify such parameters in patients of Truskavets resort who received complex drinking balneotherapy.…”
Section: Inroductionmentioning
confidence: 96%
“…"Myroslava" and "Khrystyna" mineral waters have both similar and different effects on the body of rats [1,11,12,24] and humans [8,13,14,25]. It is important that the differences are manifested not only in the severity of changes in the registered parameters, but also in their direction.…”
Section: Discussionmentioning
confidence: 99%